2013
DOI: 10.1116/1.4799352
|View full text |Cite|
|
Sign up to set email alerts
|

Strain- and kinetically induced suppression of phase separation in MBE-grown metastable and unstable GaInAsSb quaternary alloys for mid-infrared optoelectronics

Abstract: The authors have examined the dependence of phase separation in thick layers (1 μm) of molecular beam epitaxially grown, thermodynamically metastable Ga(0.25)In(0.75)As(0.22)Sb(0.78) and unstable Ga(0.50)In(0.50)As(0.44)Sb(0.56) alloys on growth kinetics and strain. For the metastable alloy, which emits at 2.8 μms, they found that phase separation does not occur for any growth temperature, and the alloy grows stoichiometrically, with step flow growth and with high optical output at around 400 °C and 440–480 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The hole barrier is composed of digitally graded three InAs/Al(In)Sb quantum wells (QWs) with well layer thickness of 83, 72, and  65 A, respectively. The electron barrier is composed of digitally graded seven GaSb/AlSb QWs with well layer thickness of 10,12,15,19,25,36 and  53 A, respectively, which is significantly thicker than the electron barrier with fewer GaSb/AlSb QWs in our previous ICIPs [1,2] and should be sufficient to force electrons move towards the preferred direction.…”
Section: Device Structures and Materials Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…The hole barrier is composed of digitally graded three InAs/Al(In)Sb quantum wells (QWs) with well layer thickness of 83, 72, and  65 A, respectively. The electron barrier is composed of digitally graded seven GaSb/AlSb QWs with well layer thickness of 10,12,15,19,25,36 and  53 A, respectively, which is significantly thicker than the electron barrier with fewer GaSb/AlSb QWs in our previous ICIPs [1,2] and should be sufficient to force electrons move towards the preferred direction.…”
Section: Device Structures and Materials Growthmentioning
confidence: 98%
“…Although the growth of quaternary GaInAsSb alloys is challenging, especially in immiscibility regions [10,11], they have been used in IR optoelectronic devices such as lasers [12,13], thermophotovoltaics [14,15], and IR photodetectors [16][17][18]. Nevertheless, to the best of our knowledge, GaInAsSb detectors have not been reported in MWIR wavelength region beyond 3 μm even though the growth of thick GaInAsSb layer had been demonstrated on GaSb substrates with substantial strain and improved material quality [13,19,20]. Also, until this work, there has not been any study reported with bulk GaInAsSb material in ICIPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, these materials have been used in a number of successful laser diodes, as well, though the degree of phase separation and relaxation was not examined in those cases [20,21]. It has been shown that metastable and unstable GaInAsSb quaternary alloys can be grown under nonequilibrium conditions in MBE by employing low growth temperatures to limit adatom diffusion, and strain to suppress phase separation and improve material quality [22,23]. Figure 2(a) shows an optical interferometric image (Wyko NT1100 optical profiling system, 2 nm vertical resolution) of the surface of a bare quantum well sample consisting of one 14 nm 20 nm −1 Ga 0.58 In 0.42 As 0.14 Sb 0.86 / Al 0.25 Ga 0.75 As 0.02 Sb 0.98 quantum well with 100 nm Al 0.50 Ga 0.50 As 0.04 Sb 0.96 clads plus a 5 nm GaSb cap grown at 450 C. The surface has a smooth surface with a low density of small defects.…”
Section: Growthmentioning
confidence: 99%